Insect‐Specific Production of New GameXPeptides in Photorhabdus luminescens TTO1, Widespread Natural Products in Entomopathogenic Bacteria. Issue 2 (25th November 2014) - Nollmann, Friederike I.; Dauth, Christina; Mulley, Geraldine; Kegler, Carsten; Kaiser, Marcel; Waterfield, Nick R.; Bode, Helge B.
Abstract Discovery of new natural products by heterologous expression reaches its limits, especially when specific building blocks are missing in the heterologous host or the production medium. Here, we describe the insect‐specific production of the new GameXPeptides E–H (5–8) from Photorhabdus luminescens TTO1, which can be produced heterologously from expression of the GameXPeptide synthetase GxpS only upon supplementation of the production media with the missing building blocks, and thus must be regarded as the true natural products under natural conditions.